Are our kids really that angry? An empirical investigation into adolescent aggression in the South African context. - Elliott, Gary (Diplomica Verlag, 2014)
The primary objective for this study was to conduct an empirical investigation to gather information in the form of data from adolescent males and females in the Pretoria region of South Africa. Information was gathered with respects to their level of physical aggression, verbal aggression, anger, hostility and depression. The information was used to identify whether correlations exist between the three variables anger, aggression and depression for South African adolescents. Auszug aus dem Text What does the literature have to say? Introduction: Anger is the most.